Participation in Physical Education Classes and Health-Related Behaviours among Adolescents from 67 Countries - Martins, João (2022)
The present study sought to examine the associations between participation in physical education (PE) classes and a range of health-related behaviours among adolescents. Secondary analysis of self-reported data from the Global Student Health Survey, collected between 2010 and 2017 from 222,121 adolescents (N = 117,914 girls; 49.0%; aged 13-17 years) from 67 countries and five world regions, was carried out. Participation in PE classes (0, 1-2, ≥3 days/week) was the independent variable. Physical activity (PA); sedentary behaviour (SB); active travel to school; fruit, vegetables, and alcohol consumption; and smoking; as well as adopting ≥5 of these healthy behaviours; were the dependent variables. Complex samples logistic regressions were performed to explore the associations between participation in PE classes and health-related behaviours. The results revealed that 18.2% of adolescents did not take part in PE classes. A total of 56.7% and 25.1% of adolescents reported participating in PE classes on 1-2 and ≥3 days/week, respectively. Only 26.8% of adolescents adopted ≥5 healthy behaviours. Participation in PE classes was positively associated with PA, active travel, fruit consumption, and vegetable consumption (only for ≥3 days/week), but was negatively associated with meeting SB recommendations, and with not smoking (only for girls and ≥3 days/week). Overall, PE participation was positively associated with adopting ≥5 healthy behaviours, with favourable results found for those who attended more PE classes. The findings revealed a positive association between participation in PE classes and a range of health-related behaviours among adolescents. This suggests that, worldwide, quality PE should be delivered at least 3 days per week up to daily to promote healthy lifestyles among adolescents.